Kista Dentigerus - Afifah Aulia R; Indra Zachreini (Pusat Riset dan Inovasi Nasional, 2024)
One of the abnormalities in the mouth that is often found in practice is cysts. Dentigerous cysts are the most common odontogenic cysts and represent approximately 20% of all cysts surrounded by epithelium that can affect the maxillary bone. Local factors causing dentigerous cysts can be related to the development of the crown or permanent tooth and can also arise from residual enamel epithelium. Patients usually show no symptoms or are asymptomatic, so these cysts are discovered accidentally during routine dental radiology examinations. However, pain may be experienced when bone expansion or resorption of adjacent teeth occurs. The goal of treatment for dentigerous cysts is to eliminate pathological abnormalities and preserve the tooth with minimal surgical intervention. The surgical technique in patients with dentigerous cysts is enucleation and marsupialization. Complications after surgery cannot be avoided in the form of paresthesia and the appearance of scars around the incision area. The prognosis after treatment is mostly excellent, and recurrence of dentigerous cysts is very rare. However, if a cystic lesion recurs, it could be the result of incomplete removal of the cyst or incorrect diagnosis of the lesion.